Comparative study on macro-invertebrates as bio indicator from the Rivers Mawa and Ratuwa, Nepal - Gurung, Jeevan Kumar (Damak Campus Journal, 2025)
This study investigates the diversity of freshwater macroinvertebrates and their correlation with physicochemical parameters in the Ratuwa and Mawa Rivers in Nepal. These rivers, which flow through both hilly and plain regions, are significantly impacted by anthropogenic activities, including urban pollution and cultural practices. Macroinvertebrates serve as bioindicators of aquatic health, making their assessment crucial for evaluating water quality. A total of 7 species from the Mawa River and 8 species from the Ratuwa River were recorded, with Arthropoda being the dominant phylum in both rivers, followed by Mollusca and Annelida. Water samples and macroinvertebrates were collected from five stations along each river from January 2024 to March 2024. Physicochemical parameters were analyzed, including Temperature, pH, Turbidity, Conductivity, Dissolved Oxygen (DO), Total alkalinity, total hardness and Biological Oxygen Demand (BOD). Statistical analyses such as ANOVA, MANOVA, and Canonical Correspondence Analysis (CCA) revealed that Temperature, Turbidity, DO and BOD were major influencing factors in the Mawa River, whereas conductivity, alkalinity, DO, and BOD were more significant in the Ratuwa River. The analysis of similarity (ANOSIM) indicated a moderate similarity between the two rivers (R = 0.184). Comparative assessments showed that Ratuwa had a slightly higher macroinvertebrate diversity than Mawa, with variations in species distribution influenced by environmental conditions. The study highlights that macroinvertebrate diversity is affected by pollution, habitat loss due to sand mining, and industrial waste discharge. Conservation measures such as regulating sand mining, reducing pollution, and implementing sustainable management practices are recommended. This research provides baseline data for future studies and underscores the need for policy interventions to protect aquatic biodiversity in the region.